PREPARATION OF THE FUTURE TEACHER FOR THE USE OF COMPUTER EDUCATION TECHNOLOGY - A PRIORITY DIRECTION OF HIGHER EDUCATION REFORM - Красноштан, В.І.; Федоров, М.В. (Modern engineering and innovative technologies, 2023)
The main goal of informatization of education is the preparation of the future teacher for a full-fledged life and activity in the conditions of the information society, a comprehensive restructuring of the pedagogical process, increasing its quality and